Virtual Reality in Linguistic Teaching to Immigrants - Sánchez, Eduardo; Burgos, Marta; Saborido, Ana (Papanda Publisher, 2023)
The purpose of this study is to evaluate the opportunities and limitations of virtual reality for language teaching for migrants in everyday life situations where the significance of cultural background can also play a lateral role. To develop this virtual reality tool, a co-creation approach was used, involving two types of end-users: immigrants and refugees, as well as teachers and facilitators from three different parts of the world. Europe: Catalonia, Germany and Greece. To assess opportunities and constraints, a mixed qualitative and quantitative approach will be used, where end-users will be interviewed and a questionnaire will be administered to collect their evaluations. In this approach, analysing the responses from the user's perspective is essential for continuous improvement. This research is part of the European project WELCOME (Multiple Intelligence Conversation Agent Services for Reception, Management and Integration of Third Country Nationals in the EU), which aims to use technology to support the reception and integration of migrants in Europe. The results obtained from this study will help developers associated with the project to improve the technology and virtual reality to make it more accessible and user-friendly for migrants and serve as a language acquisition tool in real-life situations.